A new species of Sumapazomyia Fogaça, Couri, Pérez & de Carvalho (Diptera: Muscidae) from Colombia - Ramos-Pastrana, Yardany; Uni-Urrego, Karen Yulieth; Fogaça, João M. (Zootaxa, 2024)
Sumapazomyia Fogaça et al. 2019, is a monotypic Andean genus from the Colombian Andes. Here we described one new species of Sumapazomyia from Colombia, namely Sumapazomyia quimbaya sp. nov. (type-locality: Risaralda, Otún, Quimbaya, Santuario de Fauna y Flora Otún Quimbaya), and an identification key to segregate the two species, including color images and illustrations of male and female terminalia is given. The distribution of the two species is mapped.